MACROPRUDENTIAL INSTRUMENT INTERDEPENDENCE ON STABILITY OF FINANCIAL SYSTEMS IN INDONESIA - Efendi, Bakhtiar; Sirojuzilam, Sirojuzilam; Irsyad, Irsyad; Ruslan, Dede (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2021)
Macroprudential policy is a system-oriented policy, aimed at seeing the financial system as a whole through a top-down approach. With a top-down approach, the policies to be taken are based on the results of a comprehensive analysis of macroeconomic conditions and their impact on all risks in the financial system, including the correlation between systemic risk, market dynamics, and the choice of policies to be undertaken. This policy characteristic addresses the need for an aggregate approach in creating financial system stability. Thus macroprudential policy with top-down approach will complement microprudential policy which is focused on the bottom-up approach (through the bottom up) through deeper analysis of the risk of individual financial institutions. Macroprudential policy focus does not only cover financial institutions, but also includes other financial system elements, such as financial markets, corporations, households, and financial infrastructure. Because macroprudential policy is a policy with the ultimate goal of minimizing the occurrence of systemic risk. In some studies, ecosystem risk is defined as risk that can result in the loss of public trust and increased uncertainty in the financial system During this time to overcome the instability of the financial system, the government through the monetary authority uses monetary policy instruments to stimulate economic growth but it still causes a lot of debate. Among them is the debate that occurs with economists between using policy rules or discretion policies. In the rules-rules approach, the implementation of monetary policy refers to monetary policy based on the constant-money-growth rule. While the discretion approach refers to the monetary authority having freedom in carrying out monetary policy in accordance with the actual conditions faced by an economy (Natsir, 2008). Various studies have been carried out to prove the monetary policy instruments in influencing economic growth. In Indonesia, research conducted by Julaihah and Insukindro (2004) concluded that the money supply instrument cannot influence economic growth, while the SBI interest rate instrument is able to influence economic growth in the long run. Not only research in Indonesia.